PENGARUH KOMPETENSI, SKEPTISME PROFESIONAL, MOTIVASI, DAN DISIPLIN TERHADAP KUALITAS AUDIT KANTOR INSPEKTORAT KABUPATEN/KOTA DI BALI - Triarini, Dewa Ayu Wini; Latrini, Made Yenni (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
This study aims to determine the quality of the audit on the district inspectorate office/town in Bali through competence, professional skepticism, motivation, and discipline. This research was conducted at the office inspectorate Denpasar, Badung, Gianyar, Tabanan, Singaraja, State, Karangasem, Klungkung, Bangli. The data used in this study are primary data, the method of data collection is done by distributing questionnaires. Methods of sample collection is done by using purposive sampling with a sample size of 70 respondents. The analysis technique used is multiple linear regression analysis. Results of analysis in this research is the competence, profesinal skepticism, motivation, and discipline positive effect on audit quality. The results showed that the higher the competency of the auditor, professional skepticism, motivation and discipline as an internal auditor inspectorate officials, it will improve the quality audit inspectorate officers.
Keywords: Competence, Professional Skepticism, Motivation, Discipline, Quality Audit